Pedal to the metal: Cities power evolutionary divergence by accelerating metabolic rate and locomotor performance. (25th September 2020) - Chick, Lacy D.; Waters, James S.; Diamond, Sarah E.
Abstract: Metabolic rates of ectotherms are expected to increase with global trends of climatic warming. But the potential for rapid, compensatory evolution of lower metabolic rate in response to rising temperatures is only starting to be explored. Here, we explored rapid evolution of metabolic rate and locomotor performance in acorn‐dwelling ants ( Temnothorax curvispinosus ) in response to urban heat island effects. We reared ant colonies within a laboratory common garden (25°C) to generate a laboratory‐born cohort of workers and tested their acute plastic responses to temperature. Contrary to expectations, urban ants exhibited a higher metabolic rate compared with rural ants when tested at 25°C, suggesting a potentially maladaptive evolutionary response to urbanization. Urban and rural ants had similar metabolic rates when tested at 38°C, as a consequence of a diminished plastic response of the urban ants. Locomotor performance also evolved such that the running speed of urban ants was faster than rural ants under warmer test temperatures (32°C and 42°C) but slower under a cooler test temperature (22°C). The resulting specialist–generalist trade‐off and higher thermal optimum for locomotor performance might compensate for evolved increases in metabolic rate by allowing workers to more quickly scout and retrieve resources.